The genus Inocybe (Inocybaceae, Agaricales, Basidiomycota) in Thailand and Malaysia - Horak, Egon; Matheny, P. Brandon; Desjardin, Dennis E.; Soytong, K. (My University, 2015)
Twenty-five species of Inocybaceae are reported from Thailand and Malaysia. Thirteen are described as new from four different major clades of the family: I. errata from the Mallocybe clade, I. bicolorata and I. proxima from the Inosperma clade, I. neglecta from the Pseudosperma clade, and I. brevisquamulosa, I. fragilissima, I. latibulosa, I. lineata, I. ornata, I. parvibulbosa, I. pileosulcata, I stellata and I. thailandica from Inocybe sensu stricto. Nineteen species are documented in full, circumscribed by morphological and molecular (ITS and nLSU sequences) features. Six additional lineages are depicted in a molecular phylogenetic context but at present lack sufficient morphological data for complete description. Illustrations of anatomical features, photographs of basidiomes, and SEM images of basidiospores are presented. A key to 19 species of Inocybaceae from Thailand and Malaysia is provided.
Keywords: Ectomycorrhiza; Fagalean-dipterocarp-pine forests; Fungi; SE-Asia; Taxonomy